Carboxymethylcellulose-sodium based transdermal drug delivery system for propranolol - Krishna R.; Pandit J.K. (My University, 2025)
Propranolol, a β-adrenoceptor blocker, suffers from a high degree of first-pass metabolism resulting in very low bioavailability (< 10%) following administration with conventional oral formulations. To circumvent this significant therapeutic hurdle, we formulated a carboxymethylcellulose-sodium (CMC-Na) based transdermal system for propranolol and evaluated the patch for its in-vitro and in-vivo performance. In-vitro permeation studies using the excised hair-free rat skin model resulted in 66.54% permeation at the end of 24 h in a modified Franz diffusion cell. This zero-order permeation profile was characterized by a drug permeation rate of 52.87 ± 11.63 μg cm-2 h-1. Skin irritation studies in rats (n = 5), evaluated for flare-and-wheal with respect to a formalin control, indicated that the drug-containing patch evoked only a mild response over a 7-day period. Preliminary in-vivo studies in male albino rabbits (n = 3), indicated that plasma drug levels averaged 11.75 ± 3.40 ng mL-1 in a 24-h study period before patch removal.